1998
DOI: 10.5326/15473317-34-2-113
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal osteosarcomas in dogs: a retrospective study of 169 cases (1986-1996)

Abstract: Extraskeletal osteosarcomas (EOSs) are rare tumors that arise in various soft-tissue sites (e.g., gastrointestinal tract, subcutaneous tissue, spleen, liver, skin, kidney, urinary bladder, muscle, thyroid gland, eye, and mammary glands). Soft-tissue osteosarcomas (STOs) occur in older dogs with no sex predilection; beagles and rottweilers are at higher risk. Mammary gland osteosarcomas (MGOs) occur in older females; mixed-breed dogs, German shepherd dogs, and miniature poodles are at higher risk. The median su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
129
3
24

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(192 citation statements)
references
References 12 publications
20
129
3
24
Order By: Relevance
“…It was shown that appendicular OSA carries worse prognosis than OSA situated in the axial skeleton (Nagamine et al 2015). The less common form of canine OSA are extra-skeletal (or soft tissue) tumors that show aggressive biological behaviour with high rate of recurrences (Langenbach et al 1998, Duffy et al 2015. Histological morphology of canine OSA is heterogeneous with numerous subtypes possible to diagnose in the microscopic examination, however, histologic subtyping of these neoplasms seems not to have any prognostic value (Nagamine et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that appendicular OSA carries worse prognosis than OSA situated in the axial skeleton (Nagamine et al 2015). The less common form of canine OSA are extra-skeletal (or soft tissue) tumors that show aggressive biological behaviour with high rate of recurrences (Langenbach et al 1998, Duffy et al 2015. Histological morphology of canine OSA is heterogeneous with numerous subtypes possible to diagnose in the microscopic examination, however, histologic subtyping of these neoplasms seems not to have any prognostic value (Nagamine et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, EOS occurs mainly in older animals and is observed in several locations [23,30], especially the mammary glands [30]. Mammary gland osteosarcoma (MGO) has aggressive biological behavior, and commonly shows pulmonary metastasis [23].…”
mentioning
confidence: 99%
“…A retrospective study of extraskeletal OSA (OES) in 169 dogs and a comparative evaluation of OSA in dogs and humans described metastasis in lymph nodes, lungs, kidneys, spleen, bone marrow, tegument, but did not mention the brain (9,14). In another study of OSA in 156 dogs, brain metastasis was noticed only in the Rottweiler, what 108 suggests that biological behavior of this breed may be different (12).…”
Section: Discussionmentioning
confidence: 99%